2013 IEEE International Conference on Systems, Man, and Cybernetics 2013
DOI: 10.1109/smc.2013.162
|View full text |Cite
|
Sign up to set email alerts
|

Towards a Framework to Assess Legacy Systems

Abstract: Many organizations nowadays own a number of legacy software systems and maintain them functional to fulfill their daily business operations. However, legacy systems cannot always accommodate newly emerging business needs, thus might negatively impact organization's shares in the market. So, CEOs need to recognize the limitation of their legacy systems and identify the best action for dealing with these systems considering possible options at hand. One possible solution is to replace the entire system with bran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 2 publications
0
12
0
1
Order By: Relevance
“…Based on the kinds of literature review, the different approaches for deciding the most appropriate strategy for software maintenance have been proposed [6,7,8,9]. It was found that two essential aspects are used to decide the software maintenance recommendation i.e., business value and technical value.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Based on the kinds of literature review, the different approaches for deciding the most appropriate strategy for software maintenance have been proposed [6,7,8,9]. It was found that two essential aspects are used to decide the software maintenance recommendation i.e., business value and technical value.…”
Section: Discussionmentioning
confidence: 99%
“…It was found that two essential aspects are used to decide the software maintenance recommendation i.e., business value and technical value. The business value represents the critical of the software for an organization [1,3,6,7,8,9]. Also, the technical value represents the condition or system quality included hardware, application software and software support [1,3,6,7,9].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Beberapa model penilaian perangkat lunak yang ditujukan untuk rekomendasi evolusinya sudah pernah dikembangkan oleh peneliti sebelumnya, antara lain; reengineering [6], re-architecture [7], Service Oriented Architecture (SOA) [8]. Dari…”
Section: Pendahuluan Instruksi Presiden No3 Tahun 2003unclassified